Pengaruh Radiasi Elektromagnetik: Mengidentifikasi Faktor Utama Radiasi Pada Telepon Seluler - Iqmal Hakim; Hafzah Al Dalilah; Yusuf Apdilah; Niken Maulida (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This research explores the impact of electromagnetic radiation, especially that associated with cell phone use, on human health. Electromagnetic waves, including radio waves, have become an essential part of modern technology. Although radio waves have low energy and are generally considered harmless. However, continuous exposure over a period of time will have an impact on human health. This study highlights the debate between scientific research results and manufacturers' claims about health risks. Additional focus is given to blue light produced by cell phone screens, with an emphasis on its impact on eye health, sleep and concentration disorders. The research was conducted using qualitative methods with questionnaire data collection techniques and expert interviews. involving 14 respondents, including a resource person in the field of physics. The results showed that most respondents had a general understanding of electromagnetic radiation, although knowledge related to radiation regulation was still limited. Some respondents also reported negative effects of electromagnetic radiation, such as electrical sensitivity, which they attributed to the use of cellular phones for a certain period of time. Analysis of the questionnaire revealed that most respondents had a limited understanding of the main factors of cell phone radiation, with the majority of respondents assuming that electromagnetic radiation emanating from cell phone radio antennas caused the greatest impact on human health. This emphasizes the importance of wider socialization regarding the risks of electromagnetic radiation, especially regarding the blue light on mobile phone screens which triggers the greatest negative impact of radiation emitted by mobile phones. In addition, the need for updates in existing regulations to protect public health is imperative. This research provides a basis for improved regulations and effective guidelines to protect human health from potential risks associated with technologies that generate electromagnetic radiation in daily life.